Pelatihan Desain Grafis Berbasis CorelDRAW Untuk Meningkatkan Kompetensi Siswa Kelas XI SMK Negeri 6 Kendari - Darman D; Ashabul Kahfi; Senia S; Ildayanti I; Priagung Zafitrah; Muhammad Fathul Agli (Yayasan Daarul Huda Kruengmane, 2026)
The development of information and communication technology requires vocational education institutions to produce graduates with competencies aligned with the needs of the workforce and the creative industry. One such competency is graphic design skills, particularly in creating logos and designing simple products such as clothing (T-shirts). However, graphic design instruction in Vocational High Schools (SMK) still faces limitations in terms of materials, methods, and professional software-based training. This community service activity aims to improve the competencies of eleventh-grade students at SMK Negeri 6 Kendari through graphic design training based on the CorelDRAW application. The implementation method included preparation, training, practical guidance, and evaluation using a questionnaire. The training focused on an introduction to basic graphic design, the use of CorelDRAW tools, creating simple logos, and applying logos to clothing designs (T-shirts). The results showed that of the 32 students participating in the training, more than 80% stated that the material was easy to understand and the modules were easy to apply. Furthermore, most students experienced improved skills in designing logos and applying them to clothing designs, both in terms of tool mastery, creativity, and visual composition. Thus, this CorelDRAW-based graphic design training provides a positive contribution to improving the competencies of vocational high school students, preparing them for the world of work and the creative industry.